Bacterial strain changes during chronic otitis media surgery. Issue 9 (11th July 2017) - Kim, G J; Yoo, S; Han, S; Bu, J; Hong, Y; Kim, D-K
Abstract: Objective: Cultures obtained from pre-operative middle-ear swabs from patients with chronic otitis media have traditionally been used to guide antibiotic selection. This study investigated changes in the bacterial strains of the middle ear during chronic otitis media surgery. Methods: Pre-operative bacterial cultures of otorrhoea, and peri-operative cultures of the granulation tissue in either the middle ear or mastoid cavity, were obtained. Post-operative cultures were selectively obtained when otorrhoea developed after surgery. Results: Bacterial growth was observed in 45.5 per cent of pre-operative cultures, 13.5 per cent of peri-operative cultures and 4.5 per cent of post-operative cultures. Methicillin-resistant Staphylococcus aureus was identified as the most common bacteria in all pre-operative (32.4 per cent), peri-operative (52.4 per cent) and post-operative (71.4 per cent) tests, and the percentage of Methicillin-resistant S aureus increased from the pre- to the post-operative period. Conclusion: The bacterial culture results for post-operative otorrhoea showed low agreement with those for pre-operative or peri-operative culture, and strain re-identification was required.